LQR Based Optimal PID Controller Design for Suppression of the Jitter in Laser Beam - Turan, Harun; Engin, Seref Naci (IEEE, 2020)
In this paper, the controller designed to suppress the beam jitter using a fast streering mirror and its performance on the real system are demonstrated. The main factor of the jitter, addressed as as the shift of the center of the laser beam, is taken as atmospheric turbulence. Since a model-based controller is designed, the dynamic model of the system is obtained through system identification techniques. The PID controller coefficients designed for this model are obtained by solving Riccati equation of Linear Quadratic Regulator, which provides an optimal solution by minimizing a performance cost function. The performance results of the proposed controller are examined under the condition of atmospheric disturbance.
Keywords: FSM; atmospheric turbulance; beam jitter; LQR; optimal PID; ADAPTIVE-CONTROL; Engineering; Telecommunications